Remote Work Dynamics in Semiconductor MNCs in Klang Valley: The Impact of Work Environment, Technological Infrastructure, and Work-Life Balance on Employee Productivity Moderated by Gender - Rahman, Segufta Yasmi Abdul; Sing, Ramila Devi Ram (International Review of Management and Marketing, 2024)
The shift towards remote work has become a prominent feature of contemporary workplaces, driven by technological advancements and changing organizational paradigms. This study investigates remote work dynamics within semiconductor multinational corporations (MNCs) in Klang Valley, focusing on the interplay between work environment, technological infrastructure, work-life balance, and employee productivity. Social Exchange Theory (Blau, 1964), Operational model of analysis (Leitão et al., 2019) and Task-to-Performance Chain Theory (Goodhue and Thompson, 1995) guides the exploration of how these factors influence productivity, while Predictors and outcomes of LMX Model (Tziner et al., 2020) informs the examination of gender as a moderating factor. Utilizing a quantitative research approach, data was collected through structured surveys administered to employees of semiconductor MNCs in the Klang Valley region. The survey instrument captured key variables related to the work environment, technological infrastructure, and work-life balance. Statistical analyses, including regression modeling and moderation analysis, were employed to examine the relationships between these variables and productivity while considering gender as a moderating factor. The findings provide empirical evidence regarding the impact of the work environment, technological infrastructure, and work-life balance on employee productivity in remote settings within the semiconductor industry. Additionally, investigating gender as a moderating factor uncovers potential disparities in remote work experiences and outcomes between male and female employees. This study contributes to a deeper understanding of remote work dynamics, offering insights into organizational policies and practices to optimize productivity and foster inclusivity in remote work arrangements.